Erythema multiforme following application of hair dye - Sankha Koley; Jyotirindranath Sarkar; Sanjiv Choudhary; Suparna Dhara; Manoj Choudhury (Wolters Kluwer Medknow Publications, 2012)
Erythema multiforme (EM) is an acute mucocutaneous hypersensitivity reaction with varying degrees of blistering and ulceration. Common causes of EM are herpes simplex virus infection, mycoplasma infection, drug hypersensitivity, vaccination and drug-virus interaction. EM induced by contact dermatitis is rare. Paraphenylene diamine, a common ingredient in many hair dyes, is well known to produce allergic contact dermatitis. We report a 35-year-old lady presenting with EM following severe contact dermatitis to hair dye. So far as we know, this is the first report from India describing EM following contact dermatitis.